Effect of Additional Transglutaminase Enzymes on Physical and Chemical Properties of Kamaboko Long Jawed Mackerel Fish (Rastralliger kanagurta) - Marsanda Rizka Fauziah; RR. Juni Triastuti; Patmawati Patmawati (Interdiciplinary Journal and Hummanity (INJURITY), 2023)
Long jawed mackerel is an economically important type of fish that is widely caught and consumed in Indonesia. The diversity of processed mackerel products in Indonesia is still relatively low. One of the innovations in fish-based food processing that can be done is the use of mackerel to make kamaboko. One of the enzymes that can improve the functional properties of mackerel meat protein is the transglutaminase enzyme. This enzyme has the potential to be applied to mackerel due to the content of the amino acid lysine found in myosin and glutamine in the transglutaminase enzyme so as to produce peptide bonds that form the gel kamaboko (ashi). The purpose of this study was to determine the effect of the transglutaminase enzyme on physical and chemical properties and to determine the ideal concentration of the use of the transglutaminase enzyme in the manufacture of mackerel kamaboko in compliance with SNI Kamaboko. The method used in this research is an experimental method. Researchers used a completely randomized design (CRD) with four treatments and five replications. The treatment used was the addition of transglutaminase enzyme concentrations E0 (0%), E1 (0.1%), E2 (0.5%), E3 (1%). Kamaboko mackerel is then tested for physical properties which include appearance, folding test, bite test, and gel strength, while testing for chemical properties includes moisture, fat, and protein content. The results showed that the addition of transglutaminase enzymes to mackerel kamaboko had an effect on the texture of kamaboko. Kamaboko mackerel treated E2 and E3 is kamaboko in accordance with SNI kamaboko.